2017
DOI: 10.1039/c6tb02629j
|View full text |Cite
|
Sign up to set email alerts
|

Low-adhesive superhydrophobic surface-enhanced Raman spectroscopy substrate fabricated by femtosecond laser ablation for ultratrace molecular detection

Abstract: LAS-SERS can detect the analytes of highly diluted solutions as low as sub-pico-molar concentration from only 20 μL solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…The formation of laser‐induced periodic surface structures (LIPSS), which is first observed by Birnbaum in 1965, provides a mask‐free, nonvacuum, and low‐cost processing procedure for fabricating periodic structures on sample surfaces and exhibits powerful potential in various applications . After decades of research, multiple works have focused on LIPSS formation on a diverse range of materials . Nevertheless, this technology has always faced severe challenges, namely efficiency and quality control …”
Section: Introductionmentioning
confidence: 99%
“…The formation of laser‐induced periodic surface structures (LIPSS), which is first observed by Birnbaum in 1965, provides a mask‐free, nonvacuum, and low‐cost processing procedure for fabricating periodic structures on sample surfaces and exhibits powerful potential in various applications . After decades of research, multiple works have focused on LIPSS formation on a diverse range of materials . Nevertheless, this technology has always faced severe challenges, namely efficiency and quality control …”
Section: Introductionmentioning
confidence: 99%
“…Mostly, the laser fabricated NSs made of silver (Ag) and gold (Au) targets and are frequently tested as SERS platforms because of its intriguing plasmonic properties in the visible range . Other materials such as transition metals, semiconductors, and magnetic materials are also examined as SERS substrates after deposition of Ag or Au film/NPs (up to few nm) . Wang et al fabricated nanoripples and microcones structures on the silicon (Si) substrate using femtosecond (fs) laser ablation and used them as SERS substrates after the Ag film deposition .…”
Section: Introductionmentioning
confidence: 99%
“…Other materials such as transition metals, semiconductors, and magnetic materials are also examined as SERS substrates after deposition of Ag or Au film/NPs (up to few nm) . Wang et al fabricated nanoripples and microcones structures on the silicon (Si) substrate using femtosecond (fs) laser ablation and used them as SERS substrates after the Ag film deposition . Yang et al demonstrated the 4‐methyl benzenethiol detection using Si microsquare arrays fabricated by nanosecond laser ablation .…”
Section: Introductionmentioning
confidence: 99%
“…[23] The surface micro/nanostructures and surface low energy modification are both needed for generating superhydrophobicity. [25][26][27] However, directly using the self-cleaning property can offer more advantages for practical application of the substrate. [25][26][27] However, directly using the self-cleaning property can offer more advantages for practical application of the substrate.…”
mentioning
confidence: 99%